Les langues des familles, des langues d’assez bonne « qualité » pour l’école ? Retour sur les représentations enseignantes - Nathalie Auger (Glottopol, 2023)
In various studies (Let us compare our languages, Gypsylang, Romtels), we wanted to understand whether teachers used pupils' languages to promote support and learning. Despite the fact that the teachers had been trained in the interest and the possibilities of working with the students’ languages, in class, various data (interviews, participant observations) showed that this difficulty in taking into account the languages of the pupils came from specific teachers’ representations. Most of them had to do with perceiving pupils' languages as having not sufficient "qualities", therefore in short, as not having all the characteristics of a language to be used as a resource in the classroom. This article will therefore highlight these representations and evoke projects (MALEDIVE, SIRIUS, LISTIAC) which aim in particular to work on these representations so that students' languages can fully be considered as a useful resource for learning.